Enhanced apoptotic activity of a structurally optimized form of galectin-1. - Bättig, P; Saudan, P; Gunde, T; Bachmann, M (2004)
Galectin-1 is a homodimeric protein with potent anti-inflammatory properties due to its ability to induce apoptosis in thymocytes and T cells. The galectin-1 subunits are not covalently linked but the monomers are in a dynamic equilibrium with the dimeric form. Since the affinity of the monomers for each other is rather low (in the range of 10(-5)M), the in vivo efficacy of galectin-1 is limited because the equilibrium is shifted towards the inactive monomeric form at lower concentrations. In order to overcome this problem, we designed a covalently linked form of the dimer based on the galectin-1 crystal structure. Here we show that this irreversibly dimeric form of galectin-1 is a potent inducer of apoptosis in murine thymocytes as well as murine mature T cells at concentrations 10-fold lower than wild-type galectin-1. This structurally optimized form of galectin-1 may therefore be a potentially powerful tool to treat chronic inflammatory diseases.